Percutaneous nephrolithotomy. - Wickham, J E (1981)
A new method of removing calculi from the renal collecting system, in which the large and traumatic incision in the loin currently used is unnecessary, was attempted in 31 patients. Small dilators were introduced over a guide wire through a nephrostomy tube into the renal pelvis and a catheter inserted. The track was dilated in stages and two days later the nephrostomy tube was removed and a cystoscope introduced into the interior of the kidney. A stone basket was introduced down the operating channel of the cystoscope and maneuvered to secure the stone; the cystoscope, stone basket, and stone were then removed. The procedure failed in 11 of the 31 patients, in five because the needle could not be placed accurately initially and in six because the stone could not be removed despite the establishment of a nephrostomy track. In the remaining 20 patients the procedure was successful. This procedure is far less traumatic than the conventional operation. With the development of a flexible nephroscope and an ultrasonic stone disintegrator it will be possible also to remove larger stones and stones in the peripheral calices using this method.